Application Of The Inquiry Learning Model In Solving Social Problems In Community In Ips Lessons For View Class Students Of Elementary School - Hamka, Abdul Azis Muslimin, Muhammad Nawir (Universitas Pakuan, 2022)
This study aims to obtain an overview of the social studies learning plan using the inquiry model in solving problems in class VI, also to find out student activities through inquiry models in solving problems in class VI, and to determine student learning outcomes through inquiry models in solving problems in class. VI. This research uses descriptive qualitative. Data was collected through interviews, observation and documentation. This study uses data analysis techniques, which consist of the stages of data collection, data reduction, data presentation, and drawing conclusions. The results showed that the application of the inquiry model in the social studies learning process was reflected in the teacher's ability to arrange and design social studies learning activities to be carried out effectively and efficiently, so that students in the learning process were active creatively and thought critically and were able to solve problems. Internal barriers to the application of the inquiry model in social studies subjects, the readiness of teachers and students is not optimal, the self-confidence of students is also not ready, and sometimes the teacher does not believe in the potential of students so that the position of students in the learning process is still an object, not a subject, besides the teacher and students are not used to implementing the inkuri learning model. The barrier also seen from the external factor is the learning environment. facilitation of teaching and learning activities, inadequate school environment, incomplete learning tools, incomplete learning resources and incomplete facilities.